2022
DOI: 10.1002/2211-5463.13401
|View full text |Cite
|
Sign up to set email alerts
|

Camptothecin, triptolide, and apoptosis inducer kit have differential effects on mitochondria in colorectal carcinoma cells

Abstract: Mitochondrial fission and fusion are required for cell survival, and several studies have shown an imbalance between fission and fusion in cancer. High levels of mitochondrial fusion are observed in drug‐resistant tumor cells, whereas mitochondrial fission may be important in sensitizing tumor cells to chemotherapy drugs. Based on current knowledge, we hypothesized that different chemotherapeutics might differentially affect mitochondrial dynamics and energy production. Thus, we selected chemotherapeutics with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Camptothecin treatment of A549 cells causes DNA damage, activating DNA repair mechanisms. This activation could result in an increased demand for NAD + since the enzyme poly­(ADP-ribose) polymerase (PARP), involved in DNA repair, consumes it. As a result, NADH and NADPH levels increase, impacting cellular processes, energy production, and ultimately contributing to antitumor effects and apoptosis …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Camptothecin treatment of A549 cells causes DNA damage, activating DNA repair mechanisms. This activation could result in an increased demand for NAD + since the enzyme poly­(ADP-ribose) polymerase (PARP), involved in DNA repair, consumes it. As a result, NADH and NADPH levels increase, impacting cellular processes, energy production, and ultimately contributing to antitumor effects and apoptosis …”
Section: Results and Discussionmentioning
confidence: 99%
“…As a result, NADH and NADPH levels increase, impacting cellular processes, energy production, and ultimately contributing to antitumor effects and apoptosis. 62 Vancomycin functions as an antibiotic by binding to the terminal D-Ala-D-Ala residues, disrupting the synthesis of the bacterial cell wall. 63−65 However, it also has nonantibiotic effects, such as inhibiting the mitochondrial complex I enzyme that exerts a critical role in energy production and cellular respiration.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In addition to the aforementioned small molecules of natural origin, the chemotherapeutic drugs triptolide and camptothecin, myoferlin inhibitor YQ456, and apoptosis inducer kit (AIK) stimulate DRP1 S616 phosphorylation and DRP1 S637 dephosphorylation. This dual action results in sustained mitochondrial fission, ultimately leading to cell death [ 73 , 74 ] (Fig. 2B ).…”
Section: Altered Mitochondrial Fusion–fission Dynamics In Crcmentioning
confidence: 99%
“…Accumulating evidences revealed that triptolide has a strong antitumor effect in a broad range of cancers, including non-small cell lung cancer (Zhou et al, 2022c), colorectal cancer (Liskova et al, 2022;Song et al, 2022), hepatocellular carcinoma (Li et al, 2022b), acute myeloid leukemia (Chen et al, 2022b;Kang et al, 2022b) and so on.…”
Section: Triptolidementioning
confidence: 99%
“…For the malignant melanoma treatment, targeted delivery of triptolide was applied with cyclopeptide and αvβ3 integrin-specific exosomes ( Gu et al, 2022 ). Accumulating evidences revealed that triptolide has a strong antitumor effect in a broad range of cancers, including non-small cell lung cancer ( Zhou et al, 2022c ), colorectal cancer ( Liskova et al, 2022 ; Song et al, 2022 ), hepatocellular carcinoma ( Li et al, 2022b ), acute myeloid leukemia ( Chen et al, 2022b ; Kang et al, 2022b ) and so on.…”
Section: Natural Products Undergoing Clinical Evaluation In Pancreati...mentioning
confidence: 99%